Serum Levels of Mitochondrial Fission- and Fusion-Related Genes of Coal Workers’ Pneumoconiosis and Risk Factor Analysis Based on a Generalized Linear Model - Xiao-Yu Li; Jing-Lin Wei; Yong-Xin Xie; Ji Zhao; Li-Ya Ma; Na Zhang; Hui-Fang Yang (Applied Bionics and Biomechanics)
Objective. We aimed to explore the risk factors for coal workers’ pneumoconiosis and to further explore the significance of mitochondrial fission and fusion factors in CWP and verify the feasibility of mitochondrial fission and fusion factors as diagnostic and therapeutic targets. Methods. The data of 168 cases were collected, and they were divided into a healthy control group (40 cases), dust exposure control group (61 cases), and CWP group (67 cases) and entered into SPSS 24.0. The statistical data were analyzed by the chi-square test or Fisher’s exact probability method. The variables with statistically significant differences of the univariate analysis results were included in the generalized linear model. Test level was α=0.05. Blood samples were collected to detect the ROS content, MDA content, and SOD activity. The mRNA expression levels of OPA1, Drp1, MFN2, Fis1, Col I, Col III, and α-SMA were determined by q-PCR. The protein expression levels of OPA1, Drp1, MFN2, Fis1, Col I, Col III, and α-SMA were detected by western blot. Results. Generalized linear regression analysis showed that lower school education, no respiratory protective measures, the working age beyond 15 years, and the type of work like coal mine drillers were the risk factors for CWP. With the aggravation of CWP, the degree of fibrosis and inflammation increased oxidative damage, increased mitochondrion division, and decreased fusion, which were more sensitive in the second and third stages of CWP. Conclusion. The results in this found that mitochondria are injured by fission and fusion in the CWP patients. Detection of the mitochondria fission and fusion factors provides the application value to evaluate the injury degree and progress of CWP and the clues for finding the real and effective screening and diagnosis biomarkers.